Multisituated : Ethnography as Diasporic Praxis - Sunder Rajan, Kaushik, 1974- (Book collections on Project MUSE., 2021)
"Kaushik Sunder Rajan proposes a reconceptualization of ethnography as a multisituated practice that speaks to the myriad communities of accountability and the demands of doing and teaching anthropology in the twenty-first century."--